Electronic atlas of the Russian Arctic coastal zone - Drozdov, D. S.; Rivkin, F. M.; Rachold, Volker; Ananjeva-Malkova, G. V.; Ivanova, N. V.; Chehina, I. V.; Koreisha, M. M.; Korostelev, Yu. V.; Melnikov, E. S. (Geo-Marine Letters, 2005)
A set of digital maps including geology, Quaternary sediments, landscapes, engineering-geological, vegetation, geocryological and the series of regional sources have been selected to characterize the Russian Arctic coast. Based on this data, new maps of engineering geocryological zoning and zoning of the coast with respect to the intensity of exogenous geological processes and risk of technogenic impacts have been generated at the scales of 1:4,000,000–1:8,000,000. These maps are a tool to assess the impact of industry on the Arctic coast of the country.